Construction and scaling up of solvent-free essential oils extractor - Nurul Nadiah Binti Mohamad Nizam (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Improvement of extraction process have been done and continuously starting with a conventional hydro-distillation process until the latest technology involving microwave extraction. A few factors that lead to this study are the inefficiency of conventional methods such as yield is not 100% pure and also take longer time. This study introduces new extraction technology that can solve the problem arise. The imperative key in designing this extractor is pressure and temperature. Designing and scaling up solvent-free extractor involved vessel sizing, impeller design, choosing suitable heat exchanger and calculating heat mass transfer inside extractor. Thus, the extractor with 0.305 m diameter and 0.46 m in height is designed equipped with helical ribbon as the impeller. A few conventional methods like hydro-distillation and Soxhlet had been done to Baeckea frutescens and Citrus sinensis in order to compare the samples extracted with sample from solvent-free laboratory scale extractor. The percentage of linalool contain in B. frutescens from laboratory scale solvent-free extraction is 0.11% and 51.80% limonene for C. sinensis. In addition, comparing between laboratory scales and scaled up extraction of C. sinensis the percentage of yield from scaled-up extractor is only 0.49% of 2 kg orange peel while 2.05% from 10 g of laboratory scale extractor. But the percentage of limonene content is nearly 100% with 99.96% in scaled-up extraction process sample compared to the laboratory scale which only 51.80%. The immediate observation was done and from the observation, it does shows the sample from solvent-free extraction does have last longer pleasant smell and appeared colourless. The purity of essential oils from solvent-free extraction method is preserved as no solvent being used and no additional process involved.